2010
DOI: 10.1002/cyto.a.20915
|View full text |Cite
|
Sign up to set email alerts
|

Nuclear genome size: Are we getting closer?

Abstract: Correct information on genome size is important in many areas of research. For a long time, scientists have been struggling to understand the reason for the huge variation in eukaryotic genome size and its biological significance. More recently, the knowledge on genome size has become important to structure genome sequencing projects as their scale and cost depend on genome size. Despite the fact that the first estimates of genome size in eukaryotes were made more than 50 years ago, we are still not quite sure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
134
1
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 168 publications
(153 citation statements)
references
References 80 publications
4
134
1
2
Order By: Relevance
“…Nevertheless, flow cytometry is not without its problems and careful application of the technique is essential for generating reliable data (Doležel et al 2007a;Greilhuber et al 2007). Indeed, there are multiple factors that can affect the reliability of C-value data, including the choice of extraction buffer (with over 28 different buffers in use; Lourerio et al 2007), how raw FCM data are analyzed (forward scatter, side scatter and relative fluorescence intensity), which plant species are used as calibration standards (Doležel and Greilhuber 2010;Suda and Leitch 2010) and the potentially confounding effects of cytosolic compounds (e.g. anthocyanin and tannic acid) (Doležel et al 2007a(Doležel et al , 2007bBennett and Leitch 2011;Loureiro, Suda, et al 2007;Loureiro, Rodriguez, et al 2007;Greilhuber et al 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, flow cytometry is not without its problems and careful application of the technique is essential for generating reliable data (Doležel et al 2007a;Greilhuber et al 2007). Indeed, there are multiple factors that can affect the reliability of C-value data, including the choice of extraction buffer (with over 28 different buffers in use; Lourerio et al 2007), how raw FCM data are analyzed (forward scatter, side scatter and relative fluorescence intensity), which plant species are used as calibration standards (Doležel and Greilhuber 2010;Suda and Leitch 2010) and the potentially confounding effects of cytosolic compounds (e.g. anthocyanin and tannic acid) (Doležel et al 2007a(Doležel et al , 2007bBennett and Leitch 2011;Loureiro, Suda, et al 2007;Loureiro, Rodriguez, et al 2007;Greilhuber et al 2007).…”
Section: Introductionmentioning
confidence: 99%
“…This pattern receives two reference designations internal standard, when extraction of the cores and the analysis of sample and standard are performed simultaneously, or when an external standard is performed separately. The internal standards are most recommended, especially in high-precision measurements, because the peaks of the standard used and the sample appear in the same histogram and are treated under identical conditions [26] thereby reducing possible errors due to oscillation of the device during the evaluation of the samples. However [27] reported that the simultaneous processing of the sample and the reference standard was not necessary to obtain reliable estimates of DNA.…”
Section: Reference Standards Fluorochromesmentioning
confidence: 99%
“…Feulgen densitometry (FD) and flow cytometry (FC) are the two mostly used methods in DNA content estimation. The latter has been used to estimate the nuclear DNA content and genome size of an unknown sample comparing with a reference standard (GALBRAITH et al, 1983;DOLEŽEL et al, 1998;GREILHUBER, 2010;TİRYAKİ;TUNA, 2012). Different fluorochromes (fluorescent dyes) are used in FC.…”
Section: Introductionmentioning
confidence: 99%